2014
DOI: 10.1002/chem.201402916
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate‐Triggered Self‐Assembly of N‐[(Uracil‐5‐yl)methyl]urea: A Minimalistic Urea‐Derived Hydrogelator

Abstract: N-[(Uracil-5-yl)methyl]urea is reported as a minimalistic low-molecular-weight hydrogelator (LMWHG). The unusual phosphate-induced assembly of this compound has been thoroughly investigated by IR, UV/Vis, and NMR spectroscopy, electron microscopy, and rheological experiments. This rare example of an anion-triggered urea-based LMWHG is the first example of a pyrimidine- and urea-containing molecule that can be forced into self-assembly in aqueous solution without additional aromatic or lipophilic groups. The ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 129 publications
0
9
1
Order By: Relevance
“…24 Additionally, a sustained linear viscoelastic region was found between 0.01-1% (see S3, ESI †). Our G 0 data (1.5 Â 10 4 Pa) is lower than the gels (10 6 Pa) as reported Kleinsmann 25 and Yu, 24 but greater than the G 0 100 Pa of gels as reported by Ren 26 for a Gemcitabine LMWG. An increase in the moduli with increasing concentration of linifanib was also observed which has likewise been shown for other LMWGs, for example the simple chiral bisureas of Rodriguez-Llansola et al 27 Additionally, in a similar manner to Adams et al, 28 we evaluated the power law relationship between G 0 and gelator concentration i.e.…”
contrasting
confidence: 64%
“…24 Additionally, a sustained linear viscoelastic region was found between 0.01-1% (see S3, ESI †). Our G 0 data (1.5 Â 10 4 Pa) is lower than the gels (10 6 Pa) as reported Kleinsmann 25 and Yu, 24 but greater than the G 0 100 Pa of gels as reported by Ren 26 for a Gemcitabine LMWG. An increase in the moduli with increasing concentration of linifanib was also observed which has likewise been shown for other LMWGs, for example the simple chiral bisureas of Rodriguez-Llansola et al 27 Additionally, in a similar manner to Adams et al, 28 we evaluated the power law relationship between G 0 and gelator concentration i.e.…”
contrasting
confidence: 64%
“…There are many other hydrogelators based on the urea motif developed during this decade. 243 256 For example, John et al reported a urea-containing hydrogelator, 1-[3-(decyloxy)phenyl]urea ( 25 ( n = 10)) that not only forms a hydrogel in water at 0.1 wt %, but also serves as a matrix for preparing and stabilizing gold nanoparticles by in situ reduction. 257 Steed et al reported the gelation ability of a series of chiral bisurea gelators ( 26 ).…”
Section: Molecular Designmentioning
confidence: 99%
“…Although this self-healing property has been extensively reported for polymeric systems, [13][14][15][16][17] there are fewer reports for LMW gels. [9][10][11] Pertinent examples are dipeptide gels (Fmoc-Leucinylglycine and Fmocphenylalaninylphenylalanine) which have been shown to recover after shear in similar experiments. Additional literature supports the mechanism for self-healing gels being associated Please do not adjust margins…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 99%
“…the ability to reform after application of high shear. [9][10][11] This ability for recovery after high shear is particularly relevant for injectable gels sheared through a needle as following injection the gel would be required to revert back to its original state. Indeed the self-healing properties of LMWGs is uncommon 12 when compared to the reported self-healing of polymer hydrogels.…”
Section: Introductionmentioning
confidence: 99%